SN 2023xwi: Forbidden line emission in the peak spectrum of a Ca-strong transient - Touchard-Paxton, C. -G.; Frohmaier, C.; Pursiainen, M.; Sullivan, M.; Polin, A.; Dimitriadis, G.; Galbany, L.; Killestein, T. L.; Kumar, A.; Lyman, J. (Oxford University Press (OUP), 2025)
We present an extensive optical photometric and spectroscopic investigation into the calcium-rich supernova (SN) - SN 2023xwi. Observations from a variety of ground-based telescopes follow the SN from 8 d pre-peak brightness to 87 d post-peak, covering both early-time (photospheric) and late-time (nebular) phases of the SN. Objects of this class are characterized by nebular spectra that are dominated by [Ca II] lambda lambda 7291, 7324 emission. SN 2023xwi displays a unique peculiarity in that its forbidden [Ca ii] feature is visible in its peak photospheric spectrum - far earlier than expected in current models. This is one of the strongest and earliest detections of this feature in Ca-rich SNe in photospheric-phase spectra. We investigate the velocity evolution of this spectral feature and show that it cannot be easily explained by conventional progenitor systems. From our observations, we propose an SN progenitor embedded in an environment polluted by a recurrent He-nova AM CVn system.